Factors predisposing farmers to organic fertilizer use in Oyo State Nigeria (2005)
The acceptance and continuous use of any innovation is the aim of every extension program. There are various factors which predispose farmers to the adoption of any innovation. This study was therefore carried out to find out what factors would favourably dispose farmers to the adoption of a newly introduced commercially produced organic fertilizer. The study was carried out 3 years after the introduction of the organic fertilizer in the three vegetation zones of the state. A total of 110 farmers were interviewed of which 51 used the fertilizer. Personal characteristics of farmers which were found to significantly influence the use of the organic fertilizer were age of the farmer, ownership of the farmland, level of education, social participation and knowledge of the benefits of organic fertilizers. An average of 2 bags was used, with a mean area of 0.57 hec cultivated with the fertilizer. Majority (84.30%) used out of curiosity.